Cardiorespiratory and sensory responses to exercise in adults with mild cystic fibrosis - Quon, Bradley S. (J Appl Physiol (1985), 2015)
The purpose of this study was to evaluate cardiorespiratory fitness and reasons for exercise curtailment in a contemporary adult cystic fibrosis (CF) cohort with mild lung disease. Adults with mild CF (n = 19, forced expiratory volume in 1 s = 95 ± 17% predicted) were age-, sex-, ethnicity-, and body mass index-matched to healthy controls (n = 19) and underwent a detailed cardiopulmonary cycle exercise test. While CF subjects had a reduced peak oxygen uptake compared with controls, the values were normal when expressed as %predicted in 14/19 (74%) of subjects. Both groups demonstrated a normal cardiovascular limitation to exercise and stopped exercise primarily because of leg fatigue. Despite not being exercise-limited by respiratory factors, there was some evidence of ventilatory abnormalities as patients with mild CF had increased end-inspiratory lung volumes and reached an inflection/plateau in tidal volume relative to minute ventilation at lower exercise intensities compared with controls. Subjects with CF were not more likely to demonstrate expiratory flow limitation compared with controls and did not have evidence of dynamic hyperinflation during exercise. Despite increased end-inspiratory lung volumes and an earlier tidal volume inflection/plateau, CF subjects did not experience higher levels of dyspnea. In an exploratory analysis, a significant inverse correlation was observed between sweat chloride and peak work rate. Adult CF subjects with relatively well preserved spirometry have normal exercise performance relative to reference values and are primarily limited by nonrespiratory factors. However, ventilatory abnormalities were detected even in this mild CF cohort and should be evaluated in future therapeutic trials focused on disease-modifying therapies in mild CF.